Evaluation of reference genes for reverse transcription quantitative real-time PCR (RT-qPCR) studies in Silene vulgaris considering the method of cDNA preparation - Koloušková, Pavla; Stone, James D; Štorchová, Helena (PloS one, 2017)
Accurate gene expression measurements are essential in studies of both crop and wild plants. Reverse transcription quantitative real-time PCR (RT-qPCR) has become a preferred tool for gene expression estimation. A selection of suitable reference genes for the normalization of transcript levels is an essential prerequisite of accurate RT-qPCR results. We evaluated the expression stability of eight candidate reference genes across roots, leaves, flower buds and pollen of Silene vulgaris (bladder campion), a model plant for the study of gynodioecy. As random priming of cDNA is recommended for the study of organellar transcripts and poly(A) selection is indicated for nuclear transcripts, we estimated gene expression with both random-primed and oligo(dT)-primed cDNA. Accordingly, we determined reference genes that perform well with oligo(dT)- and random-primed cDNA, making it possible to estimate levels of nucleus-derived transcripts in the same cDNA samples as used for organellar transcripts, a key benefit in studies of cyto-nuclear interactions. Gene expression variance was estimated by RefFinder, which integrates four different analytical tools. The SvACT and SvGAPDH genes were the most stable candidates across various organs of S. vulgaris, regardless of whether pollen was included or not.
Keywords: sekvenční analýza RNA; rostlinné geny; DNA, Complementary; Gene Expression Profiling; Reverse Transcriptase Polymerase Chain Reaction; Genes, Plant; kvantitativní polymerázová řetězová reakce; Silene; polymerázová řetězová reakce s reverzní transkripcí; komplementární DNA; Sequence Analysis, RNA; stanovení celkové genové exprese; Real-Time Polymerase Chain Reaction